Os fundamentos da teoria do abuso do direito - Fernandes, Deborah Fonseca (2016)
The purpose of this work is to present the elements that structure the theory of abuse of right in the current Brazilian law from the analysis of the expressions contained in article 187 of the Civil Code of 2002, that is, what is Law and right, the object of abuse, good faith, morality and the social and economic role of right, which are expressed limits imposed by law. In addition, there are, briefly, the historical development of the theory, the doctrinal currents on the subject and its design in Portuguese civil law. It sought through research in national and foreign doctrines clarify the contents of vague terms used for the characterization of the abuse of rights theory and the difficulties to accept it because of the apparent conformation behavior with a subjective right prescribed by law. Through the doctrinal and jurisprudential study presents the foundations of theory and its practical importance for solving social disputes. Thus, it can be seen that the theory is not merely ideal, but with relevance to be effective, in some cases, the only tool able to facilitate the restoration of the legal relationship to that expected by law